2016
DOI: 10.21037/jtd.2016.12.22
|View full text |Cite
|
Sign up to set email alerts
|

LMO4 is a prognostic marker involved in cell migration and invasion in non-small-cell lung cancer

Abstract: Background: The aims of this study were to analyze the association of LMO4 with non-small-cell lung cancer (NSCLC) survival rate, and to determine its functional role and signaling pathway in lung cancer. Methods: Immunohistochemistry (IHC) was used to detect the expression of LMO4 in NSCLC cell lines and tumor tissues. Migration and invasion ability was detected respectively by wound healing test and transwell test. Immunofluorescence and western blot were detected of AKT/PI3K pathway related genes MAPK, PI3K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…In addition, Lmo4 can inhibit differentiation of mammary epithelial cells, and its high expression promotes breast cancer by repressing tumor suppressor BRCA1-mediated transcriptional activation (Visvader et al, 2001; Sum et al, 2002). Lmo4 is also involved in the tumorigenesis of pancreatic cancer (Yu et al, 2008) and non–small cell lung cancer (Wang et al, 2016). Several studies reported that Lmo4 is highly expressed in ILCs and their progenitors (Robinette et al, 2015; Gury-BenAri et al, 2016; Seillet et al, 2016; Harly et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Lmo4 can inhibit differentiation of mammary epithelial cells, and its high expression promotes breast cancer by repressing tumor suppressor BRCA1-mediated transcriptional activation (Visvader et al, 2001; Sum et al, 2002). Lmo4 is also involved in the tumorigenesis of pancreatic cancer (Yu et al, 2008) and non–small cell lung cancer (Wang et al, 2016). Several studies reported that Lmo4 is highly expressed in ILCs and their progenitors (Robinette et al, 2015; Gury-BenAri et al, 2016; Seillet et al, 2016; Harly et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…LMO4 functioned as an oncogene in diverse cancers, and high expression of LMO4 was linked to poor prognosis and low survival. 29 , 30 In mechanism, LMO4 interacted with proteins involved, among else, in tumorigenesis, such as P53. 31 Besides, a previous study demonstrated that LMO4 was targeted by miR-139-5p, and circRNA-BACH2 facilitated PTC deterioration by activating the expression of LMO4 by targeting miR-139-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, LMO4 expression is raised in Burkitt lymphoma cells and LMO4 depression impairs the cell ability of migrating and accelerates cell apoptosis 30 . What is more, it is displayed that LMO4 maintains a high expression in nonsmall cell lung cancer cells and tissues, which is involved in disciplining cell migration and invasion 31 …”
Section: Discussionmentioning
confidence: 99%
“…30 What is more, it is displayed that LMO4 maintains a high expression in nonsmall cell lung cancer cells and tissues, which is involved in disciplining cell migration and invasion. 31…”
Section: Discussionmentioning
confidence: 99%